PENERAPAN NATURAL LANGUAGE PROCESSING DALAM APLIKASI CHATBOT SEBAGAI MEDIA PENCARIAN INFORMASI DENGAN MENGGUNAKAN REACT (STUDI KASUS: INSTITUT BISNIS DAN INFORMATIKA KWIK KIAN GIE) - Akhmad Budi (Institut Bisnis dan Informatika Kwik Kian Gie, 2020)
Techonological development in today have helped in field of education in terms of delivering informations.Delivery of information or the dissemination of information at this time has begun to apply computertechnology as a tool for help, but not yet supported by interactive information searching media.Using naturallanguage processing for extracting keywords from a sentence can be applied with Application ProgrammingInterface from Dialogflow and will be applied in form of a chatbot and will be built using React framework.This research will be conducted with Waterfall method, data gathering done by observation, interview, surveyand information from related parties. The chatbot or system design will be built with UML design. Chatbotapplication has successfully met the standards with the success rate of 80%. This chatbot aims to provideconvenience for students in obtaining information about academic activities.Keywords: Natural Language Processing, Chatbot, Dialogflow, React, Application Programming Interface.